Kuru Temizleme Etiketli Ürünlerin Evde Günlük Bakımı - Gürbüz, Ece (Fen Bilimleri Enstitüsü, 2015)
Günlük yaşamda tekstil ürünleri ayrılmaz bir parçamızdır. Gün boyu üzerimizde bulunan giysiler bakım yapılarak bir sonraki kullanım için hazır hale getirilirler. Her tekstil ürünü üretildiği life, formuna, aksesuarlarına ve benzeri özelliklerine göre bakım gerektirir. Bu nedenden dolayı giysilerde doğru bakım yapılabilmesi amacıyla bakım etiketleri bulunur. Bazı tekstil ürünlerinin bakım etiketlerinde ‘sadece kuru temizleme’ ibaresi bulunmaktadır. Bu ürünler genellikle suyun zarar vereceği düşünülen ürünlerdir. Kuru temizleme işleminin ana aşamaları ön işlem (leke çıkarma), temizleme ve ütülemedir. Özellikle muamele edilecek giysi leke barındırıyorsa bir leke çıkarıcı / kimyasal kullanılması gerekmektedir ve giysi makinede işlem görmesi öncesinde ön işleme tabi tutulmalıdır. Kuru temizleme işleminde yaygın olarak kullanılan perkloretilen solventinin zararlarından dolayı kuru temizleme işlemine alternatif yöntemler de geliştirilmiştir. Bunlardan biri de ıslak temizlemedir. Islak temizleme işleminde çözücü olarak solvent kullanılmaz. Bunun yerine sulu ortamda liflerin zarar görmesini engelleyici çeşitli kimyasallar ve çok hasssas hareketler yapan bilgisayar kontrollü makineler kullanılır. Bu bilgilerin ışığında ‘sadece kuru temizleme’ etiketli ürünlerin evde bakımı üzerine çalışmalar yapılmıştır. Hassas tekstil ürünlerinin ev tipi makinelerde uygun bir şekilde muamele edilebilmesi için gerekli koşulların belirlenmesi amaçlanmıştır. Ev tipi makinelerde yapılacak bu işlemin tekstil ürünün formunu koruması, kırışıklık ve koku gidermesi hedeflenmiştir. Yapılan çalışmalar üç ana sınıfa ayrılabilir. Bunlar, ön çalışmalar, piyasadaki benzer amaç taşıyan ev tipi ürünlerin incelenmesi ve ana çalışmadır. Ön çalışmalarda, 11 kg çamaşır makinesi ve 7 kg ısı pompalı buharlı kurutma makinesi kullanılmıştır. Yapılan ön çalışmaların sonucunda, giysi formunun bozulmadan korunması açısından kurutma makinesinin daha etkili olduğu belirlenerek, çalışmalara kurutma makinesinde devam edilmiştir ve bu çalışmalarda ısı pompalı kurutma makinesinde buharın kırışıklık açmada etkili bir parametre olduğu ortaya koyulmuştur. Ayrıca yapılan çalışmalarla kırışık açmada gerdirmenin de önemli bir parametre olduğu belirlenmiştir. Piyasadaki diğer ürünlerin araştırmasında dolap tipi bir ürün ve tek parça giysi için tasarlanmış bir ürün test edilmiştir. Tek parça giysi için tasarlanan üründe kıyafet, farklı yönlerdeki mandallar ile gerdirilerek asılmakta, 10 dakika süresince bir kapsül yardımıyla hoş koku verilmektedir. İncelenen dolap tipi ürün ise, tazeleme, kırışıklık giderme, hijyen ve kurutma fonksiyonlarına sahip kabin tipi ısı pompası sistemi ile çalışan bir üründür. Ürünün yükleme kapasitesi 5 kg’dır. Cihazda bulunan buhar ünitesi ile koku molekülleri yok edilerek tazeleme yapılmaktadır. Kırışıklık açma buhar yardımıyla gerçekleştirilmektedir. Bakteriler buhar ve sıcak hava ile yok edilerek hijyen sağlanmaktadır. Deneysel çalışma bölümünde, ön çalışmada edinilen bilgilerden faydalanılarak bir deney tasarımı yapılmıştır. Deney tasarımında kullanılan parametreler buhar süresi, buhar debisi ve yerleşim olarak belirlenmiştir. Bunun yanı sıra kuru temizleme etiketli özelliğe sahip %100 ipek gömlek ve %100 keten gömlek olmak üzere iki ayrı tekstil tipi ile çalışılmıştır. Deneyler 7 kg ısı pompalı buharlı kurutma makinesinde yürütülmüştür. İncelenen deney çıktıları, % koku uzaklaştırma, kırışıklık ve boyutsal değişimdir. Ölçüm için AATCC strandartları kullanılmıştır. Koku uzaklaştırma etkisi hem sübjektif hem objektif olarak değerlendirilmiştir. Subjektif değerlendirme Arçelik Merkez Ar-Ge’de geliştirilen yönteme göre panelistler tarafından yapılmıştır. Objektif değerlendirme için ise GC-MS cihazı kullanılmıştır. Deney sonuçları Minitab 17 programı kullanılarak değerlendirilmiştir. Yapılan analize göre her iki kumaş tipi için de kırışıklık gidermede en etkin parametrenin yerleşim olduğu belirlenmiştir. Yapılan optimizasyon çalışmaları sonucunda ipek gömlek ve keten gömlek için birer adet optimum koşul belirlenmiştir. Belirlenen optimum koşullarda yapılan test sonuçları, benzer amaçlı ticari ürünlerle kıyaslandığında koku uzaklaştırma performansı açısından benzer sonuçlar elde edildiği, kırışıklık giderme performansının ise incelenen ticari ürünlere göre daha iyi olduğu belirlenmiştir. Geliştirilen algoritmaların kullanımı ve ütüleme işleminin enerji tüketimiyle, konvansiyonel yıkama, kırıtma ve ütüleme işleminin enerji tüketimi ve süreleri kıyaslanmıştır. Buna göre geliştirilen algoritmalar ütüye harcanan süreyi yıkama ve kurutma işlemi sonrasında ütülemeye göre oldukça kısaltmıştır. Harcanan enerji miktarı da diğer işlemlere kıyasla belirgin seviyede düşüktür. Deneyler esnasında belirli bölgelere yapay kırışıklıklar yapılarak çalışılmıştır. İpek ve keten için geliştirilen optimum işlem koşulları belirlendikten sonra numuneler bir gün giyilimiş ve üzerlerinde oluşan doğal kırışıklıklar ile deney yapılmıştır. Bu deneylere göre de belirlenen optimum koşulların deneyler esnasında kullanılan yapay kırışıklık oluşturulmuş numunelerle örtüşen sonuçlar verdiği görülmüştür.

Textiles are the integral parts of our daily lives. Clothes which we wear all day, need to be maintained for the next usage. Every textile product need to be cared according to their features like its fiber, form, accesories and other specialities. Due to this reason, there are care labels on garments with the purpose of accurate maintenance. Sometimes, there could be ‘dry clean only’ expression on the care labels. Generally, these labels belong to the clothes which might be affected by water adversely. They become more sensetive to abrasion when they absorb water. Water is not used in dry cleaning. In the cleaning phase of dry cleaning, generally perchloroethylene is used as main washing medium. There are three main phases of dry cleaning. These stages are, pretreatment (stain removal), cleaning and ironing. Especially, if the garment has a stain, a pretreatment process is required before the dry cleaning operation. One or more chemicals might be used for the pretreatment process. However, perchloroethylene is a solvent which is harmful for human health. Therefore, some other alternative cleaning methods are developed to solve this problem. One of these methods is wet cleaning. In wet cleaning process, water is used as medium instead of the solvent. Some chemicals are added in water for preventing shrinkage, felting and other damages that arise from water. Moreover this process is done by computer controlled machines which make sensetive movements. In the light of this information, studies were conducted on home care of garments that have ‘dry clean only’ care label. Determining the requirements of suitable treatment of delicate clothes in domestic machines was intended. It was aimed to maintain the textile products’ form, remove the wrinkles and odors by using this domestic treatment. These studies can be devided in three parts. These are, the preliminary studies, analysis of the domestic products with similar objectives and the main study. In preliminary studies, 11 kg washing machine and 7 kg heat pump drying machine were used. In washing machine, some detergents were examinated by using a gentle washing programme. In drying machine some home dry cleaning kits and different drying styles with different conditions were tested. At the end of these studies, the drying machine was determined to be more effective in terms of protection against deterioration of the garment forms and the rest of the studies were performed in the drying machine. In these studies, it revealed that the steam is an effective parameter for removing wrinkles. Moreover, it was determined that, also stretching is a significant factor for wrinkle removal. A product which is designed for a single cloth and a cabinet type product were examinated in the scope of the analysis of other products. A garment is stretching with latches and treated with a chemical during 10 minutes for wrinkle removal and giving fragrance in the single garment type product. The cabinet type product is a device which works with a heat pump system and has refreshment, wrinkle removal, hygiene and drying functions. Loading capacity of the product is 5 kgs. Refreshment is performed by a steam unit of the device. This process includes elimination of odor molecules. Also, wrinkle removal process is done by steam. Moreover, hygiene is provided by eliminating bacteria due to the steam and hot air. In the main study section, a design of experiment is created by using the outputs of preliminary studies. Design parameters were steam duration, steam flow rate and textile placement in the tumble dryer. The resulting set of experiments were done with 100% silk shirt and 100% linen shirt, individually. Experimentals were carried out in 7 kg heat pump tumble drier. Odor removal percentage, wrinkle recovery and dimentional change are the outputs of experiments. Odor removal performance was evaluated both subjectively and objectively. Subjective evaluation was performed by panelists. They compared treated samples with referances and numerate them according to their odor intensity. After the programme optimization, odor removal performance of determined programme was done objectively. GC-MS was used for the objective measurement of odor removal percentage. AATCC appearance of fabrics after repeated home laundering replicas were used for wrinkle evaluation. Residual wrinkle amount of threated shirts were scored according to this replicas. Dimentional changes were determined by measuring length and width of the shirts before and after the tumble drier process. No significant dimentional change was determined. Minitab 17 was used for analysis of experimental results. According to the analysis, it was determined that the most effective parameter is textile placement for wrinkle removal, for both silk and linen. Afterwards the analysis, optimization studies were conducted for determining the optimum process parameters. In the end of the optimisation, two optimum algorithms were determined one each for silk and linen shirts. For silk, 18 minutes steam duration, 19.7 g/min steam flow rate and stretching; for linen, 18 minutes steam duration, 25.5 g/min steam flow rate and free settlement conditions were optimum. Similar odor removal performance results were obtained when optimum test results were compared with other commercial products. While commercial product removes %90 of odor, optimum condition removes %88.3 of odor. Furthermore, wrinkle removing performance of optimum conditions were better than this commercial products. While the wrinkle score of the shirts which processed with determined condion were 4.2, the score of commercial product was 3. The energy consumption and time duration of the determined optimum programmes with subsequent ironing and convantional washing, tumble drying, ironing processes were compared. It was shown that processing with optimum programmes shorthened the ironing time. Besides, energy consumptions of the optimized conditions were signally decreased. 79 minutes were spent for washing, tumble drying and ironing silk shirts, although 23,5 minutes were spent for determined programme on tumble dryer and ironing of silk shirts. Energy consumptions were 0.526 kWh and 0.245 kWh respectively. Washing, tumble drying and ironing took 78 minutes for linen shirt and process of optimum programme and ironing continued 24 minutes. For the process including washing, tumble drying and ironing consumed 0.637 kWh, determined optimum programme and ironing spent 0.299 kWh energy. During the experimentals, wrinkles were made artificially at specified locations. After determining the optimum processing conditions, this conditions were tested with natural wrinkles of one day worn silk and linen shirts. The results of natural wrinkle specimens coincided with artificial wrinkled specimens. According to this comparison, natural wrinkled specimens had same recovery results for linen shirt. Besides, recovery results of silk shirts were better than artificial ones. Because for silk specimens daily wrinkles were smoother than the linens.
Home Care Of Dry Cleaning Labeled Products
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2015
Keywords: kuru temizleme; hassas tekstil; bakım; keten; ipek; kırışıklık; koku; dry cleaning; delicate textile; care; linen; silk; wrinkle; odor